EXPLORING CITY BRANDING FOR TOMOHON - Imbar, Hanna R. K.; Tulung, Joy E.; Tielung, Maria V. J. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Abstract: City branding is not only the main identity of a city, but also serves as an eye-catching advertisement to attract the tourists. Unfortunately, there was a city that created their own city branding without considering their own characteristics. For example, Tomohon city. At this moment, Tomohon is well known as a city of flowers, city of tourism, city of education, and religious city. Tomohon does not have a specific branding that can reflect the potential and values, and that can represents the expectations of the inhabitants. The purpose of this study is to explore city branding of Tomohon. The operational definitions of this research are people, place, pulse, potential, presence, and prerequisite. This research used qualitative methodology by using interview method. This research took 15 representative respondents of governments, students, entrepreneurs, religionists, cultural observers, visitors, and academicians of Tomohon city. The findings of this research show that Tomohon was a friendly city, both for human or nature, which has rapid development in the fields of education and technology, and has strong potential to become an ecotourism city. City branding for Tomohon that the researcher humbly proposes is "The heart of North Sulawesi."Â Keywords: city branding, tomohon, people, place, potential, pulse, presence, prerequisite, .